PKM Kelompok Usaha Roti dan Kue : Optimalisasi Produk dan Proses Produksi Berbasis Pemanfaatan Teknologi Tepat Guna di Desa Pesucen dan Desa Kalipuro Kecamatan Kalipuro Kabupaten Banyuwangi Provinsi Jawa Timur - Qiram, Ikhwanul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Micro, Small and Medium Enterprises (UMKM) in Banyuwangi have a proportion of 99.81% compared to largeand medium industries which amount to 0.19%. The types of bread and cakes UMKM develop along with the busyness of thecommunity and the dynamics of social life. This Community Partnership Program (PKM) aims to increase the knowledge andproductivity of the Micro Business Bread and Cake Group in the village of Pesucen and Kalipuro Village, Kalipuro District,Banyuwangi Regency. This PKM activity is carried out by holding a vertical mixer dough mixer and an automatic heat regulating bread oven. The next step is to carry out production management and bookkeeping training activities as well as operating training and equipment tools. With the support of this activity, it is expected to increase the productivity of the business being developed expected to improve production and management capacity so as to accelerate business development. This development is also expected to be able to open employment opportunities